2020
DOI: 10.1002/glia.23834
|View full text |Cite
|
Sign up to set email alerts
|

Microglia senescence occurs in both substantia nigra and ventral tegmental area

Abstract: During aging humans lose midbrain dopamine neurons, but not all dopamine regions exhibit vulnerability to neurodegeneration. Microglia maintain tissue homeostasis and neuronal support, but microglia become senescent and likely lose some of their functional abilities. Since aging is the greatest risk factor for Parkinson's disease, we hypothesized that aging‐related changes in microglia and neurons occur in the vulnerable substantia nigra pars compacta (SNc) but not the ventral tegmental area (VTA). We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 53 publications
(65 reference statements)
6
29
0
Order By: Relevance
“…Consistent with the literature, we observed age‐related differences in microglia associated with increased microglial activation. For control animals, we confirmed an age‐related increase in Iba‐1 expression in the hippocampus, increased number of CA1 microglial cells, and a slight reduction in microglial branch length, consistent with microglial activation (Chan et al, 2018; Damani et al, 2011; Hefendehl et al, 2014; Perkins, Piazza, & Deak, 2018; Shaerzadeh et al, 2020; Tremblay, Zettel, Ison, Allen, & Majewska, 2012). Similarly, we confirmed an age‐related decrease in CA1 synaptic transmission (Barnes, Rao, & Shen, 1997; Billard & Rouaud, 2007; Bodhinathan et al, 2010; Kumar & Foster, 2013), which may be linked to microglial activation (Barter et al, 2020; Kim et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with the literature, we observed age‐related differences in microglia associated with increased microglial activation. For control animals, we confirmed an age‐related increase in Iba‐1 expression in the hippocampus, increased number of CA1 microglial cells, and a slight reduction in microglial branch length, consistent with microglial activation (Chan et al, 2018; Damani et al, 2011; Hefendehl et al, 2014; Perkins, Piazza, & Deak, 2018; Shaerzadeh et al, 2020; Tremblay, Zettel, Ison, Allen, & Majewska, 2012). Similarly, we confirmed an age‐related decrease in CA1 synaptic transmission (Barnes, Rao, & Shen, 1997; Billard & Rouaud, 2007; Bodhinathan et al, 2010; Kumar & Foster, 2013), which may be linked to microglial activation (Barter et al, 2020; Kim et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
“…No additional morphological measures significantly varied between the groups. In conclusion, microglia exhibited a strong impact of aging, with greater microglial activation indicated as more microglia and shorter branches (Hopperton, Mohammad, Trépanier, Giuliano, & Bazinet, 2018; Shaerzadeh et al, 2020; Streit et al, 2004; Streit & Xue, 2013). PLX3397‐treated young and aged animals exhibited microglial depletion, and aged depleted rats had the fewest microglia along with shorter branches.…”
Section: Resultsmentioning
confidence: 99%
“…We did not detect substantial neuron loss in the VTA/SNc by 18mo of age ( Fig. 7 ), in agreement with other reports 62,63 , suggesting that early increases in microglial abundance are unlikely to be caused by neuronal death in these brain regions. Although systemic inflammation can promote microglial proliferation 64 , we did not detect increases in plasma levels of inflammation until 24mo of age, well after increased VTA/SNc microglial proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…S1 ). Several studies have reported no change in substantia nigra 33 , progressive decreases in substantia nigra 61 , or transient decreases in VTA and SNc microglial number during aging 62 . These studies generally rely on Iba1 immunostaining, which may be more difficult to accurately quantify than genetically-encoded fluorescent markers.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular differences between the different states of the microglia under these different settings remain to be resolved.In addition to microglia being hypophagocytic, we show that coculture of microglia with P301S tau aggregate-containing neurons induced the hypofunctional microglia to secrete several senescence-associated factors (CXCL1, CXCL2, CCL5, IGFBP3, MMP9, and MMP3 (62)). The presence of dystrophic microglia that have been linked to senescence have been reported in Alzheimer's disease and other neurodegenerative disorders(63)(64)(65)(66) although no molecular signatures of senescence were recorded. Loss of phagocytic capacity, increased SA-β-gal activity, and altered cytokine profiles such as those we describe here are common signs of senescence.…”
mentioning
confidence: 99%